INVESTIGATION OF THE RELATIONSHIP BETWEEN MUSCULAR PAIN AND FATIGUE STRENGTH IN HEALTHCARE PROFESSIONALS - Erdoğan, Meryem; yasemin (Göbeklitepe Medical Science Journal, 2024)
The study was conducted to examine the relationship between musculoskeletal pain and fatigue severity in healthcare professionals. The research is of descriptive type and was applied to all healthcare professionals working in a public hospital of a province in the Black Sea region between 20 March and 20 April 2023 and accessible online. All healthcare workers who could be reached and accepted in the study were included in the study, and sampling was not selected. To get data; Individual Identification Form, Visual Analogue Scale, and Fatigue Severity Scale were used. Of the 238 health workers, 76.5% are female, and 23.5% are male in the study. It was determined that of the health workers, 50.8% were nurses, 49.58% were and 76.1% had musculoskeletal pain. The mean musculoskeletal pain severity score was 4.15±2.76 and the Fatigue Severity Scale mean score was 4.91±1.58, and the fatigue severity rate was found to be high in healthcare workers with musculoskeletal pain (p<0.001). The study showed that there is a relationship between musculoskeletal pain and fatigue severity in healthcare workers. Therefore, it is thought that musculoskeletal pain will decrease when the workload of healthcare workers is reduced and appropriate working conditions are provided.